2013
DOI: 10.1038/modpathol.2013.48
|View full text |Cite
|
Sign up to set email alerts
|

PCR detection of clarithromycin-susceptible and -resistant Helicobacter pylori from formalin-fixed, paraffin-embedded gastric biopsies

Abstract: Antimicrobial resistance to clarithromycin is a growing concern in the treatment of Helicobacter pylori and is associated with three major point mutations of the 23S rRNA, A2142C, A2142G, and A2143G. The use of traditional culture-based methods for determination of clarithromycin resistance in H. pylori are time consuming and lack sensitivity. We implemented a real-time PCR with melt curve analysis to detect and characterize H. pylori in formalin-fixed, paraffin-embedded gastric biopsy specimens to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
2
11
0
2
Order By: Relevance
“…In our study, mutation A2142C was not found in any patient, A2143G and A2142G mutations were found to be the most frequent. There are several other studies whose results are consistent with our study 20,28,[29][30][31] . The eradication ratio was lower for patients detected to have A2143G mutation 29 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our study, mutation A2142C was not found in any patient, A2143G and A2142G mutations were found to be the most frequent. There are several other studies whose results are consistent with our study 20,28,[29][30][31] . The eradication ratio was lower for patients detected to have A2143G mutation 29 .…”
Section: Discussionsupporting
confidence: 83%
“…It is an advantage of this method to be able to determine the possible effect of clarithromycin resistance in the failure of treatment through the biopsy samples of previously applied treatments retrospectively. It is reported that concerning the formalin-fixed, paraffin-embedded gastric biopsies, the sensitivity of the PCR method can be enhanced through optimal control of time of fixation by formalin and proper choice of paraffin sections 28 . PCR method is particularly more effective in identifying H.pylori infection for cases having less number of bacteria 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopsy-based testing is commonly performed to detect early H. pylori infection34. This panel of tests includes culture5, urease test6, histology7 and PCR8, all of which provide direct and accurate information. However, biopsy is an invasive and tedious procedure, requiring endoscopy that is prone to missing small lesions and making the patient uncomfortable.…”
mentioning
confidence: 99%
“…Several PCR-based methods have been developed for rapid detection of antibiotic resistant H. pylori strains [15,16]. Several PCR-based methods have been developed for rapid detection of antibiotic resistant H. pylori strains [15,16].…”
Section: Diagnosis Of H Pylori Infectionmentioning
confidence: 99%